Avaliação de risco à saúde humana decorrente da contaminação da água subterrânea por BTEX provenientes de postos de revenda de combustíveis em Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2010)
Nowadays, Manaus has 175 gas stations, and it is estimated that de lifespan of them, that is around 25 years it is near to the end. This increase the probability of gasoline spills that contains Benzene, Toluene, Methylbenzene and Xylenes (BTEX), and, because of their toxicity and potentially adverse health effects it may become a risk for the general population, if groundwater is contaminated. Hence, the main goal of this study was estimate BTEX exposure through groundwater, as well as the human health risks associated with this exposure. A total of 38 gas stations were visited, and samples of groundwater were taken. Samples were analyzed by gas chromatography fitted with a flame ionization detector (FID), after headspace solid phase microextraction. Human exposure was estimated as a combination of three pathways: inhalation, direct ingestion, and dermal absorption during bath for adult men and women, children and babies. Deterministic and probabilistic risk was assessed. Cancer risk for benzene was estimated in 70% of gas stations from south zone and in 40% from north zone, for all genders and ages. At central-south and west zone, no cancer risk associated with benzene was determined. Cancer risk for benzene was estimated to be between 5xE−05 and 105xE−05 above the limit value of 1xE-05. The children were exposed a higher risks. Non-cancer risk associated with benzene were determined in North and South zones, and associated with xylenes in CentralSouth zone. For probabilistic assessment the 95th percentile of risk was estimated to be 6E−05, indicating that cancer risk is not negligible. Non-carcinogenic risks for toluene, ethylbenzene, and xylenes were lower than the specified level of 1.0. Since health risk associated to BTEX was identified, a monitoring routine need to be implemented by environmental and public health agencies.
Keywords: Águas subterrâneas - Poluição; Combustíveis – Aspectos ambientais; Combustíveis – Avaliação de risco; Groundwater - pollution; Fuels- environmental aspects; Fuels- Risk assessment; CIÊNCIAS AGRÁRIAS